Peripherality as key to understanding opportunities and needs for effective and sustainable climate-change adaptation: a case study from Viti Levu Island, Fiji. (25th November 2020) - Korovulavula, Isoa; Nunn, Patrick D.; Kumar, Roselyn; Fong, Teddy
ABSTRACT: A study of various defining aspects of 11 rural communities along the cross-island road on Viti Levu (Fiji) shows diversity attributable largely to their peripherality, proxied by distance along this 200-km long road. Strong relationships are found between peripherality and both community size and the dependency ratio (percent of young/old dependents), as well as traditional medicine usage (and percent traditional healers), and autonomous community coping after disasters. Two measures are calculated to capture community autonomy, both of which proxy peripherality. Results show the usefulness of peripherality as a way of measuring community diversity in developing-country contexts. Peripherality also correlates with community autonomy, more-peripheral communities having greater autonomous coping abilities/capacity than near-core (less-peripheral) communities. Results also show the unhelpfulness of the default '"one-size-fits-all'" approach to communities implicit in many external assistance programs. Yet while traditional coping in such communities may not be able to fully overcome future climate-change challenges, the conservation of the traditional knowledge underpinning this should be encouraged, mainly because of the likelihood that external funding for future adaptation in such communities will be inadequate. The best hope for effective and sustainable adaptation to future climate change, focused on sustaining livelihoods, lies in strengthening autonomous community coping.